Tellurium-capped carbon rods: syntheses and electronic and structural properties - Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank (Organometallics, 2003)
The synthesis of bis(methyltelluro)alkynes with two (2), three (3), and four (4) alkyne units was achieved. The key step was the reaction of the corresponding bis(trimethylsilyl)alkynes 10−12 with methyllithium, tellurium, and methyliodide in a one-pot reaction. The structures of 2−4 as well as that of bis(methyltelluro)acetylene (1) were investigated in the solid state. All four samples showed C2 symmetry in the solid state. For 1−4 we found relatively short Te···Te contacts of two neighbors, giving rise to a zigzag arrangement between the Te centers and forming stacks of molecules. The He(I) and He(II) photoelectron spectra of 1 as well as the UV/vis spectra of 1−4 are reported and discussed.